Teknologi penguraian limbah jamur untuk peningkatan varian produksi petani jamur Desa Umbansari - Dianita Wardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Oyster mushrooms are one type of mushroom that is cultivated commercially in Indonesia. Oyster mushroom is one type of mushroom that is commercially cultivated in Indonesia. Oyster mushrooms can be harvested within 1-3 months. So that from the business side of oyster mushrooms is very profitable. Namur because the business capital to buy mushroom seeds supplied from outside the area is reduced, then from 5 mushroom farmers who survive only 2 farmers. One of them is in the village of Umban Sari Atas, Rumbai District, Pekanbaru City. For this reason, a larger business capital is needed than before. This is where the idea arises to increase the variation in production from the mushroom. One of them is using baglog mushroom waste which has not been utilized into mushroom baglog briquettes. By using baglog waste technology, oyster mushrooms can be broken down and converted into mushroom baglog briquettes. The oyster mushroom baglog waste briquettes of course can be one of the alternative fuels that can be sold and made into a variant of production other than mushrooms. Thus it is expected to increase the income of mushroom farmers. In this PKM some of the problems faced are: (1) increased utilization of baglogjamur waste as a product variant of fungal development that has not been utilized or baglog waste in order to increase production and income. (2) Procurement of manual press machines to get the same baglog mushroom briquette density. The output of this PKM is the introduction of oyster baglog mushroom waste decomposition technology as the development of mushroom products and the manufacture of mushroom briquettes to oyster mushroom farmers in Upper Umban Sari village and the procurement of manual press machines for making baglog mushroom briquettes. In addition, from the PKM, there is an increase in the production of mushroom farmers, if previously the farmers can harvest 3-4 kg of mushrooms a day, now farmers can harvest mushrooms 5-6 kg per day. After using the combustion process using briquettes from processed baglog mushroom waste, farmers can also save costs for purchasing fuel (wood, rice husk) of Rp. 120,000 for the process of heating and steam mushroom seeds every month.